Prevalence and patterns of symptoms of dysautonomia in patients with long‐COVID syndrome: A cross‐sectional study. Issue 6 (8th April 2022) - Eldokla, Ahmed M.; Mohamed‐Hussein, Aliae A.; Fouad, Ahmed M.; Abdelnaser, Mariam G.; Ali, Sara T.; Makhlouf, Nahed A.; Sayed, Islam G.; Makhlouf, Hoda A.; Shah, Jaffer; Aiash, Hani
Abstract: Background: The association between autonomic dysfunction and long‐COVID syndrome is established. However, the prevalence and patterns of symptoms of dysautonomia in long‐COVID syndrome in a large population are lacking. Objective: To evaluate the prevalence and patterns of symptoms of dysautonomia in patients with long‐COVID syndrome. Methods: We administered the Composite Autonomic Symptom Score 31 (COMPASS‐31) questionnaire to a sample of post‐COVID‐19 patients who were referred to post‐COVID clinic in Assiut University Hospitals, Egypt for symptoms concerning for long‐COVID syndrome. Participants were asked to complete the COMPASS‐31 questionnaire referring to the period of more than 4 weeks after acute COVID‐19. Results: We included 320 patients (35.92 ± 11.92 years, 73% females). The median COMPASS‐31 score was 26.29 (0–76.73). The most affected domains of dysautonomia were gastrointestinal, secretomotor, and orthostatic intolerance with 91.6%, 76.4%, and 73.6%, respectively. There was a positive correlation between COMPASS‐31 score and long‐COVID duration ( p  < 0.001) and a positive correlation between orthostatic intolerance domain score and post‐COVID duration ( p  < 0.001). There was a positive correlation between orthostatic intolerance domain score and age of participants ( p  = 0.004). Two hundred forty‐seven patients (76.7%) had a high score of COMPASS‐31 >16.4. Patients with COMPASS‐31 >16.4 had a longer duration of long‐COVID syndrome than those with score <16.4 (46.2 vs. 26.8 weeks, p  < 0.001). Conclusions: Symptoms of dysautonomia are common in long‐COVID syndrome. The most common COMPASS‐31 affected domains of dysautonomia are gastrointestinal, secretomotor, and orthostatic intolerance. There is a positive correlation between orthostatic intolerance domain score and patients' age.